Anticoagulation Management in Patients With Atrial Fibrillation and Cirrhosis. Issue 4 (1st May 2021) - Shenoy, Abhishek; Jarava, David; Stotts, Matthew J.; Intagliata, Nicolas M.
Abstract : Watch a video presentation of this article Watch the interview with the author